Casual Factors and Sanctions For Disciplinary Violation Of School Rules - Amelia, Nadila; Amelia, Nisa; Nurhaliza (International Journal of Education and Teaching Zone, 2023)
This study discusses the factors that cause disciplinary violations against governance school rules and sanctions. This research is motivated by the effectiveness of the procedure discipline in enforcing student discipline in schools. As is known that the rules in the school environment are a set of rules and regulations that have been made by the school to create a conducive and representative atmosphere in the school environment. This type of research is qualitative research. As for who became the population of the research subjects was students of MAN 2 Jambi City, Kec. South Jambi, taking the sample in the form of 31 people consisting of 26 female students and 5 students. Instrument data collection in this study by distributing questionnaires. Then for data analysis use the google form that has been distributed to the samples. The results of this study data obtained that the factors causing disciplinary violations of school rules are the need and the biggest sanction given in the form of a warning letter.